Effects of biogenic silver and iron nanoparticles on soybean seedlings (Glycine max) - Guilger-Casagrande, Mariana [UNESP]; Bilesky-José, Natália; Sousa, Bruno Teixeira; Oliveira, Halley Caixeta; Fraceto, Leonardo Fernandes [UNESP]; Lima, Renata (Springer Nature, 2022)
Background: Biogenic metallic nanoparticles have been emerging as a promising alternative for the control of phytopathogens and as nanofertilizers. In this way, it is essential to investigate the possible impacts of these new nanomaterials on plants. In this study, the effects of soil contamination with biogenic silver (AgNPs) and iron (FeNPs) with known antifungal potential were investigated on morphological, physiological and biochemical parameters of soybean seedlings. Results: The exposure of plants/seedlings to AgNPs induced the reduction of root dry weight followed by oxidative stress in this organ, however, adaptive responses such as a decrease in stomatal conductance without impacts on photosynthesis and an increase in intrinsic water use efficiency were also observed. The seedlings exposed to FeNPs had shown an increase in the levels of oxygen peroxide in the leaves not accompanied by lipid peroxidation, and an increase in the expression of POD2 and POD7 genes, indicating a defense mechanism by root lignification. Conclusion: Our results demonstrated that different metal biogenic nanoparticles cause different effects on soybean seedlings and these findings highlight the importance of investigating possible phytotoxic effects of these nanomaterials for the control of phytopathogens or as nanofertilizers.
Keywords: AgNPs; Biogenic metallic nanoparticles; FeNPs; Lignification; Phytotoxicity; Soybean